Spatio-temporal analysis of foraging behaviors of Anelosimus studiosus utilizing mathematical modeling of multiple spider interaction on a cooperative web. (7th November 2016) - Quijano, Alex John; Joyner, Michele L.; Ross, Chelsea; Watts, J. Colton; Seier, Edith; Jones, Thomas C.
Abstract: In this paper, we develop a model for predation movements of a subsocial spider species, Anelosimus studiosus . We expand on a previous model to include multiple spider interaction on the web as well as a latency period during predation. We then use the model to test different spatial configurations to determine the optimal spacing of spiders within a colony for successful capture during predation. The model simulations indicate that spiders uniformly spacing out along the edge of the web results in the most successful predation strategy. This is similar to the behavior observed by Ross (2013) in which it was determined to be statistically significant that during certain times of the day, spiders were positioned along the edge more than expected under complete spatial randomness. Abstract : Highlights: A stochastic model for predation movement of A. studiosus with multiple spider interaction during predation is developed. The model is simulated under different spatial configurations for varying colony sizes to test the success of prey capture. Simulation indicates that spiders uniformly spacing out on the edge of the web is the most successful predation strategy.